Planning and analyzing clinical trials with composite endpoints - Rauch, Geraldine; Schüler, Svenja; Kieser, Meinhard (Springer, 2017)
Preface -- Contents -- Part I General Introduction to Composite Endpoints -- 1 Definition and Rationale -- 2 Challenges of Composite Endpoints -- 3 Guideline View - Recommendations and Requirements -- 4 Clinical Trial Examples -- Part II Confirmatory Test Problem for a Single (Composite) Endpoint -- 5 The Single-Stage Design -- 6 Group-Sequential and Adaptive Designs -- 7 Related Software Code -- Part III Confirmatory Multiple Test Problem -- 8 Correlation Between Test Statistics -- 9 The Single-Stage Design -- 10 Group-Sequential and Adaptive Designs -- 11 Related Software Code -- Part IV Confirmatory Test Problem for a Weighted Composite Endpoint -- 12 Weighted Binary Composite Endpoint -- Weighted Time-to-Event Composite Endpoint -- 14 OtherWeighted Effect Measures -- 15 Related Software Code -- Part V Descriptive and Confirmatory Evaluation of the Components -- 16 Descriptive Analysis of the Components -- 17 Supplementary Confirmatory Analyses of the Components -- 18 Related Software Code -- Part VI Illustrating Clinical Trial Examples -- 19 Clinical Trial Examples with Binary (Composite) Endpoints -- 20 Clinical Trial Examples with (Composite) Time-to-Event Endpoints